MOG-IgG myelitis coexisting with systemic lupus erythematosus in the post-partum setting. (July 2020) - Bilodeau, Philippe A; Kumar, Vinayak; Rodriguez, Andrew E; Li, Clarence T; Sanchez-Alvarez, Catalina; Thanarajasingam, Uma; Zalewski, Nicholas L; Flanagan, Eoin P
Background: Longitudinally extensive transverse myelitis (LETM) accompanying systemic lupus erythematosus (SLE) is often due to coexisting aquaporin-4-IgG seropositive neuromyelitis optica spectrum disorder but has not been associated with myelin oligodendrocyte glycoprotein-IgG (MOG-IgG). Objective and methods: Case report at an academic medical center. Results: A 32-year-old woman developed severe transverse myelitis (paraplegia) shortly after SLE onset in the post-partum period. Magnetic resonance imaging (MRI) revealed an LETM, cerebrospinal fluid showed marked inflammation, and testing for infections was negative. Serum live-cell-based assay for MOG-IgG was positive but aquaporin-4-IgG was negative. Conclusion: In patients with SLE and LETM, MOG-IgG testing should be considered, in addition to AQP4-IgG.